On long-distance theta-role assignment - Saab, Andrés Leandro (2015)
In this paper, the long-standing assumption that (External or Internal) Merge is a necessary condition for theta-role assignment is challenged. It is argued, then, that a theory of thematic assignment which allows for long-distance theta-role assignment under conditions of locality and activity is empirically preferable when it comes to some complex interactions between se and causative constructions in Buenos Aires Spanish. It is also shown that recent arguments against long-distance theta-role assignment do not hold in a theory as the one defended here, which conceives of theta-roles as regulated by conditions generally available in the realm of A-dependencies.